2020
DOI: 10.1002/jcph.1724
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal and Childhood Outcomes in Offspring of Pregnant Women Using Antidepressant Medications: A Critical Review of Current Meta‐Analyses

Abstract: This article reviewed the results of 21 recent meta‐analyses examining the relationship between maternal use of antidepressants during pregnancy and negative outcomes in newborns and children. PubMed was searched for meta‐analyses published in English between January 1, 2011, and November 30, 2019, by using combinations of the keywords pregnancy, antidepressants, review, meta‐analysis, selective serotonin reuptake inhibitors, selective serotonin‐norepinephrine reuptake inhibitors, tricyclic antidepressants, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…What is not understood is the mechanism underlying these findings. There is much recent research investigating relationships between antidepressant medications and ASD ( 94 , 95 ) but despite the positive associations, a causal link has not been firmly substantiated. Much less is known about such a relationship with ID ( 96 ).…”
Section: Discussionmentioning
confidence: 99%
“…What is not understood is the mechanism underlying these findings. There is much recent research investigating relationships between antidepressant medications and ASD ( 94 , 95 ) but despite the positive associations, a causal link has not been firmly substantiated. Much less is known about such a relationship with ID ( 96 ).…”
Section: Discussionmentioning
confidence: 99%
“…8 Results have largely been conflicting, and whether antidepressant exposure increases the risk of these childhood disorders remains controversial. 8 It is possible that confounding by indication of antidepressants for severe depression and by genetic and environmental factors associated with NDDs in children can explain the observed associations. 9 Moreover, few studies have considered other specific diagnosed NDDs outside of small, hospital-or clinicbased settings.…”
mentioning
confidence: 99%
“…A moderately increased risk of neonatal and childhood outcomes in children (e.g., preterm birth, low birth weight or autism) exposed to antidepressants in utero was reported, although some meta‐analyses outlined that these increased risks of complication were no longer significant when compared to a group of untreated depressed mother–child pairs. Thus, the author of this review article including 21 meta‐analyses concluded that it is difficult to disentangle whether underlying mechanisms are related to medication or maternal psychiatric disorders 24 . In contrast, Xing and colleagues concluded in their meta‐analysis (including 48 cohort and 6 case–control studies) that children exposed to antidepressants during pregnancy had increased risks of preterm birth, low birth weight and admissions to neonatal intensive care units compared with newborns of depressed but unmedicated mothers.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the author of this review article including 21 meta-analyses concluded that it is difficult to disentangle whether underlying mechanisms are related to medication or maternal psychiatric disorders. 24 In contrast, Xing and colleagues concluded in their meta-analysis (including 48 cohort and 6 case-control studies) that children exposed to antidepressants during pregnancy had increased risks of preterm birth, low birth weight and admissions to neonatal intensive care units compared with newborns of depressed but unmedicated mothers. Risks of spontaneous abortions, low APGAR scores at 5 min or neonatal convulsions were higher when mothers were treated with antidepressant medication during pregnancy compared to newborns of healthy mothers.…”
Section: Yesmentioning
confidence: 98%